Query complexity of approximate equilibria in anonymous games - Goldberg, P; Turchetta, S (Elsevier, 2017)
We study the computation of Nash equilibria of anonymous games, via algorithms that use adaptive queries to a game’s payoff function. We show that exact equilibria cannot be found via query-efficient algorithms, and exhibit a two-strategy, 3-player anonymous game whose exact equilibria require irrational numbers. We obtain positive results for known sub-classes of anonymous games. Our main result is a new randomized query-efficient algorithm for approximate equilibria of two-strategy anonymous games that improves on the running time of previous algorithms. It is the first to obtain an inverse polynomial approximation in poly-time, and yields an efficient polynomial-time approximation scheme.